Recurrent spontaneous abortions, Hashimoto thyroiditis and alopecia totalis: response to anticoagulation and intravenous immunoglobulin therapy. (February 2014) - Bozic Antic, Ivana; Macut, Djuro; Popovic, Bojana; Isailovic, Tatjana; Petakov, Milan; Ognjanovic, Sanja; Damjanovic, Svetozar
Abstract Introduction: Although numerous studies indicated a link between antithyroid antibodies and recurrent spontaneous abortions (RSA), consensus on the treatment of this condition is still lacking. Case report: We present a case of a 35-year-old pregnant woman (gestation week 4) with primary hypothyroidism, total alopecia, high level of positive antithyroid antibodies, and history of two recurrent spontaneous abortions in early pregnancy. Along with L-thyroxin substitution, intravenous human immunoglobulin (IVIg) combined with anticoagulation and antiaggregation therapy was introduced. During pregnancy her scalp hair completely re-grew, and following gestation week 39 she delivered healthy female child. Conclusion: Thyroid antibodies could contribute to previous recurrent abortions in our patient. It is suggested that in older primiparas with Hashimoto thyroiditis and history of RSA, a combined treatment with IVIg, anticoagulation and antiaggregation therapy should be considered.